Numerical and experimental assessment of hydrogen enrichment effects on ci engine characteristics fuelled with dual biodiesel blends: A comprehensive study - B. Vishnu Vardhana Naidu; B. Musthafa; M. Raja; S. Sivalakshmi; S. A. Srinivasan; B. Saravanan; Yohanis Dabesa Jelila (PLoS ONE, 2026)
The growing need for energy around the world is putting pressure on established power sources like fossil fuels, making renewable energy solutions more concern. The high calorific value of hydrogen has made it an attractive technique for increasing combustion rates. To get the best possible results from a dual biodiesel blend of juliflora and kapok, this research seeks to improve the hydrogen enrichment ratio. When compared to diesel, the combined effects of 12H 2 + JK B20 increased BTE by 11.5%, CP by 6.9%, and HRR by 5.9%. The use of H 2 and JK B20 improved combustion, leading to a decrease of 8.5% in BSFC, 10.9% in CO and HC emissions, 11.5% in smoke, and 14.6% in both. The increase in NOx emissions is a result of the trade-off. The RSM results demonstrate that the test blend B20, which included 12% H 2 at 100% load, exhibited an attractiveness index of 0.995. An effective and trustworthy prediction framework for optimizing CI engine properties, the ANN model was fitted using experimental data and validated. Sustainable transportation and environmental protection stand to benefit greatly from the synergistic effects of H 2 enrichment and dual biodiesel.